Fundamental Factors Influencing Investments in Mutual Funds – The EIC Approach: A Case Study of RCAML - Viyyanna Rao, K.; Daita, Nirmala (Indian Journal of Finance, 2012)
The Indian mutual fund industry is witnessing a rapid growth as a result of infrastructural development, increase in personal financial assets, and rise in foreign participation. There are many factors contributing to this phenomenon. The present research is an attempt to analyze the influence of fundamental factors such as economy, industry and company on the performance of mutual funds. Effort has been made to carry out an in-depth analysis of the economy through a collection of monthly data pertaining to the key macro-economic variables covering a period of 228 months spread over 19 years. The causal relationship between real economic variables and their impact on the performance of mutual funds has been studied with the help of descriptive statistics consisting of suitable test statistics, correlation matrix, Augmented Dickey-Fuller (ADF) test, and Granger’s causality test. To appraise the mutual fund industry in a lucid style, various aspects such as Assets Under Management (AUM), investor type and product classification have been studied with the help of percentage analysis. Finally, the fundamental soundness of the company has been gauged against the chosen parameters with the support of descriptive statistics, correlation matrix, simple regression and multiple regressions.